Jerzy Osiatyński (1941-2022) - Toporowski, Jan (PSL Quarterly Review, 2022)
This obituary describes Jerzy Osiatyński’s life and works, recalling his origins and early life, the academic and activity, and the personal and intellectual links with Michał Kalecki.